An Efficient Method for Monitoring Predatory Minute Pirate Bugs Orius spp. (Hemiptera: Anthocoridae) Populations Using Blue-Colored Sticky Traps. Issue 2 (11th February 2019) - Furihata, Shunsuke; Tabuchi, Ken; Okudera, Shigeru; Takahashi, Akihiko; Hinomoto, Norihide; Shimoda, Masami; Yamaguchi, Terumi
Abstract: Minute pirate bugs of genus Orius (Wolff) are known important generalist predators of microinvertebrate pests and are therefore useful in many agricultural contexts. Effective sampling methods are thus of great importance to monitor Orius spp. populations. Sticky traps are one such sampling method; however, trap color must be carefully selected for the target insect species. In this study, we examined the most suitable sticky trap color (i.e., white, blue, or yellow) to capture Orius spp. individuals in eggplant Solanum melongena (Linnaeus) (Solanales: Solanaceae), Italian ryegrass Lolium multiflorum (Lamarck) (Poales: Poaceae), soybean Glycine max (Linnaeus) (Fabales: Fabaceae), and white clover Trifolium repens (Linnaeus) (Fabales: Fabaceae) fields. More Orius spp. adults were caught on blue and white traps than on yellow traps. The white traps also caught other insects, which hampered the counting of Orius spp. individuals and, therefore, reduced trapping efficiency. In addition, seasonal prevalence investigations showed that blue sticky traps had similar patterns to those of field observations. Thus, as the blue sticky trap can avoid capturing nontarget insects, we concluded that blue was the most suitable trap color for monitoring Orius spp. In addition, because blue sticky traps are more efficient and less-labor intensive, they can be useful as an alternative to field observations.